The Effect of Problem Based Learning on the Learning Outcomes of Motorcycle Machine Maintenance Lessons in Class XI TBSM SMK Medika Samarinda - Yudha Ari Purnama; Agus Perianto; Didik Cahyono (Budapest International Research and Critics University, 2021)
This study was carried out with the following objectives: 1) to determine the difference in the significance value between the Problem Based Learning (PBL) and Conventional Learning models in the subject of Motorcycle Engine Maintenance (PMSM) for Class XI TBSM SMK Medika Samarinda; and 2) to determine the effect of the Problem Based Learning (PBL) model on the learning outcomes of the Motorcycle Engine Maintenance (PMSM) subject of Class XI TBSM SMK Medika Samarinda. This type of research is quasi-experimental with the method of dividing class groups using Non-equivalent Control Group Design. The sampling technique used an assignment random sampling technique, namely using existing classes in schools with the same conditions. Data were collected using test techniques in the form of pre-test and post-test. Then the data were analyzed using the one-way ANOVA test technique with the help of the SPSS 17.0 application. The standard of significance level used in the data analysis test is 0.05. The results showed that: 1) there were significant differences between the Problem Based Learning (PBL) and Conventional Learning models in the subject of Motorcycle Engine Maintenance (PMSM) for Class XI TBSM SMK Medika Samarinda; and 2) there is an effect of the Problem Based Learning (PBL) model on the learning outcomes of the Motorcycle Engine Maintenance (PMSM) subject of Class XI TBSM SMK Medika Samarinda.